2020
DOI: 10.21203/rs.3.rs-45837/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The efficacy of mineral corticoid receptor antagonist, canrenone, in COVID-19 patients

Abstract: Purpose: Despite the spread of SARS-CoV-2 global pandemic and the volume of clinical trials launched, no specific therapeutic drug approaches improving outcomes have been so far approved. In COVID-19 patients, aldosterone via ACE2 deregulation may be responsible for systemic and pulmonary vasoconstriction, inflammation and oxidative organ damage.Aim: To verify retrospectively the impact of the mineral corticoid receptor antagonist canrerone i.v. on the need of invasive ventilatory support and/or all-cause in-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Another investigation in a cohort of 306 COVID-19 patients revealed that elevated plasma sACE2 from COVID-19 patients was significantly associated with severe forms of disease, particularly in hospitalized patients intubated at the time of sample collection (Kragstrup et al, 2021). ARDS in patients with COVID-19 was found associated with an increase in blood pressure and decrease in serum potassium concentration (Vicenzi et al, 2020). Surprisingly, another recent report suggests a significant reduction of Ang II concentration and increased Ang-(1-7) in COVID-19 patients (Martins et al, 2021).…”
Section: Modulation Of Ace2 and Other Actors Of The Ras In Covid-19 P...mentioning
confidence: 99%
“…Another investigation in a cohort of 306 COVID-19 patients revealed that elevated plasma sACE2 from COVID-19 patients was significantly associated with severe forms of disease, particularly in hospitalized patients intubated at the time of sample collection (Kragstrup et al, 2021). ARDS in patients with COVID-19 was found associated with an increase in blood pressure and decrease in serum potassium concentration (Vicenzi et al, 2020). Surprisingly, another recent report suggests a significant reduction of Ang II concentration and increased Ang-(1-7) in COVID-19 patients (Martins et al, 2021).…”
Section: Modulation Of Ace2 and Other Actors Of The Ras In Covid-19 P...mentioning
confidence: 99%